Can We Trust Open Government Data in Public Procurement? - Fritzsche, Robin; Westermann, Jan; Klassen, Gerhard; Wyszynski, Marc; Niehaves, Björn (Conference on Digital Government Research, 2025)
Evidence-based policy-making in public procurement depends on high-quality data. This case study evaluates 14 months (Nov 2023–Jan 2025) of procurement records from the EU’s Tenders Electronic Daily (TED) to assess the reliability of this key data source. Our analysis uncovers significant anomalies in data accuracy and governance, raising concerns about the integrity of procurement processes and the policies built on them. We highlight the urgent need for improved data governance to support transparency, accountability, and innovation-driven procurement.